TINDAKAN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG (PUPR) PROVINSI RIAU TERHADAP REKONSTRUKSI JALAN SELENSEN KOTABARU KABUPATEN INDRAGIRI HILIR 2022-2023 - Saputra, Dandika; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the actions taken by the Public Works and Spatial Planning Office (PUPR) of Riau Province in the reconstruction process of the Selensen–Kotabaru Road in Indragiri Hilir Regency during 2022–2023. The road reconstruction is part of the regional government's efforts to improve inter-regional connectivity and support local economic growth. This research employs a qualitative descriptive method with a case study approach. Data were collected through interviews with relevant parties, field observations, and documentation. The research findings indicate that the actions of the PUPR Office of Riau Province included technical planning, budgeting, project implementation, and work supervision. However, the implementation process faced several challenges, such as geographic conditions, budget limitations, and extreme weather, which slowed down the construction. Despite these obstacles, efforts to accelerate development were made through cross-sector coordination and adjustments to the work schedule. Overall, the road reconstruction showed significant progress over a two-year period and had a positive impact on community mobility and the distribution of agricultural products. Keywords: PUPR, Road Reconstruction, Public Policy, Regional Infrastructure